Analysis of the Legal Consequences of Legalizing Polyandry Marriages in the Gorontalo Religious Court Area - Siti Nur Magfirah A. Hudodo; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Estudiante Law Journal, 2023)
The purpose of this research is to find out the Legal Consequences of Legalizing Polyandry Marriages in the Gorontalo Religious Court Area. In this research, the author uses normative research method or normative juridical research. This normative research includes library research or document study, because the object studied is in the form of public official documents, namely official data from the Gorontalo Religious Court. The results of this study researchers found preliminary data in the Gorontalo Religious Court, there is 1 (one) case of Itsbat Nikah application which is contrary to Article 3 and Article 9 of Law Number 1 of 1974 jo. Law Number 16 of 2019 concerning Marriage, as well as Article 40 of the Compilation of Islamic Law (KHI) but by the panel of judges the case was granted and there was 1 (one) itsbat nikah case Number 255/Pdt.P/2022/PA.Gtlo with the same type of application case but there were differences in the judge's consideration in deciding the case with the ruling not accepted.